Fabrication of highly active phosphatase-like fluorescent cerium-doped carbon dots for in situ monitoring the hydrolysis of phosphate diesters. Issue 68 (14th November 2020) - Du, Jinyan; Qi, Shuangqing; Chen, Juan; Yang, Ying; Fan, Tingting; Zhang, Ping; Zhuo, Shujuan; Zhu, Changqing
Abstract : The hydrolytic cleavage of BNPP was catalyzed and monitored by the fluorescent CeCDs. Abstract : Ce-Doped carbon dots (CeCDs) were fabricated via a one-step hydrothermal carbonization using Ce(NO3 )3 ·6H2 O and EDTA·2H2 O as precursors, and various experimental techniques were employed to characterize the morphology, structure and composition of the as-obtained CeCDs. Using the disodium salt of bis(4-nitrophenyl)phosphate (BNPP) as a DNA model substrate, mimetic phosphatase activity toward phosphate ester hydrolysis cleavage was investigated. It was found that similar to the catalytic character of the natural enzyme, CeCDs as a hydrolase mimic can exhibit a good catalytic activity for promoting BNPP hydrolysis, in which metal Ce(iii ) acts as a center for binding and activation of the metal-bound hydroxide complex as well as a source of nucleophilic metal hydroxides. Additionally, based on the Inner Filter Effect (IFE), fluorescence spectra can be used to monitor the hydrolysis of BNPP using CeCDs, which mimic phosphatase. Thus, the unique properties of the CeCD mimetic phosphatases as well as the IFE sensing strategy would provide an ideal platform to monitor the catalytic phosphate ester hydrolysis processes. Finally, to validate the availability of the established catalytic systems, the CeCDs were further applied for degradation of organophosphorus pesticide chlorpyrifos. The degradation efficiency was estimated to be a satisfactory value of 74.50%, exhibiting a potential application prospect for treatment of the pollutants in the soil and water.